2022
DOI: 10.1111/1467-8489.12469
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of temperature on Chinese food processing firms*

Abstract: This article investigates the impacts of temperature variations on industrial output and accounting profits of food processing firms, using rich panel data of Chinese food processing firms for the 1998-2007 period. We find that both industrial output and accounting profits peaked at a daily average temperature of 21-24°C and declined sharply at higher temperatures. Higher temperatures reduced firms' output and profits primarily by hurting total factor productivity and reducing investment in capital and thus ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
4
1
Order By: Relevance
“…In the case of big firms, the associated coefficient is even positive (1.5%, p-value <0.10). This result differs from previous evidence on the Chinese manufacturing and food industry (Chen et al, 2022;Chen & Yang, 2019;Zhang et al, 2018), where the reduction of TFP explains, at least partially, the reduction of the output. In our case, firms could have compensated production losses by adjusting inputs or inventories.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…In the case of big firms, the associated coefficient is even positive (1.5%, p-value <0.10). This result differs from previous evidence on the Chinese manufacturing and food industry (Chen et al, 2022;Chen & Yang, 2019;Zhang et al, 2018), where the reduction of TFP explains, at least partially, the reduction of the output. In our case, firms could have compensated production losses by adjusting inputs or inventories.…”
contrasting
confidence: 99%
“…This implies that 5 days at this temperature would reduce TFP by −0.6%. Similarly, using the temperature bins approach, Chen et al (2022) find that TFP in Chinese food manufacturing decreases by about 0.4% for each day with an average temperature greater than 30°C. Multiplying it for 5 days brings it to −2%.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Firms would also change their inventory in respond to sudden extreme climate events. Chen et al (2022a) find that for each additional day when the temperature exceeds 30 °C, food processing firms will increase their inventory by 0.43%. Second, manufacturing enterprises tend to adjust financial behaviours to adapt to extreme climate risks.…”
Section: Manufacturing Enterprises' Adaptation Behaviours To Extreme ...mentioning
confidence: 98%
“…The strategy management literature has suggested that poor performance may trigger firms to carry out more innovative behaviours (Greve, 2003). As previously mentioned, extreme climate events can affect manufacturing enterprises' production operations, leading to adverse performance outputs (Chen et al, 2022a;Zhang et al, 2018). When manufacturing enterprises encounter poor performance outcomes caused by extreme climate events, they are more likely to adopt green technology innovation to improve organisational resilience, so as to build adaptability to extreme climate events.…”
Section: Potential Heterogeneitiesmentioning
confidence: 99%